2008
DOI: 10.1016/j.juro.2008.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Ureteroscopic Management of Intrarenal Calculi

Abstract: Ureteroscopy is a safe method for the treatment of intrarenal calculi in the prepubertal population. Our ureteroscopic stone-free rate for intrarenal stones is lower than that reported for ureteral stones. Parents should be informed that additional procedures will likely be required, especially in younger patients and those with stones larger than 6 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 20 publications
1
46
0
7
Order By: Relevance
“…In their series of 50 kidney stones in children with an age range of 1.2-13.6 years, Tanaka et al [32] achieved SFR with a single session in 58% and needed an additional procedure in 36% of the patients. They found that success rates were correlated with stone dimension, where need for additional procedure was correlated with both stone dimension and patient age.…”
Section: Rirs In Pediatric Patientsmentioning
confidence: 99%
“…In their series of 50 kidney stones in children with an age range of 1.2-13.6 years, Tanaka et al [32] achieved SFR with a single session in 58% and needed an additional procedure in 36% of the patients. They found that success rates were correlated with stone dimension, where need for additional procedure was correlated with both stone dimension and patient age.…”
Section: Rirs In Pediatric Patientsmentioning
confidence: 99%
“…However, no correlation was reported in that study between the complications that developed and use of ureteral access sheath or ureteral dilation. In a study from 2008, Tanaka et al [26] published the results from 50 pediatric patients with a mean age of 7.9 (1.2-13.6 years) and receiving RIRS due to renal stone. Mean stone size was 8 mm (1-16) mm; 58% of cases remained stone-free at long-term follow-up with a single procedure, while an additional procedure was required in 36%.…”
Section: Childrenmentioning
confidence: 99%
“…However, PCNL is typically reserved for larger stone burden and treatment failures of SWL and/or RIRS because of its more invasive nature. Although stone-free rates are greater than 85% after a single PCNL in children, complications including urosepsis, bleeding requiring transfusion, renal pelvis perforation, and injury to adjacent organs are not uncommon [3,4,[10][11][12]. The morbidity associated with RIRS is considerably less than that with PCNL, and the flexible ureteroscope allows access to the polar regions.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing experience of RIRS in adults, recently, a few reports of successful ureterorenoscopic management of renal stones in children have been published [1][2][3]. However, most of those reports include a significant number of older adolescents.To our knowledge, no prior study has specifically addressed the efficacy of retrograde endoscopic management of intrarenal calculi in the preschool-age children.…”
mentioning
confidence: 99%